Contribution Of God’s Servants In Upholding Sound Doctrine In The Church Community Based On Titus 1:5 - 2:10 - Robi Panggarra; Yosua Feliciano Camerling (Jurnal Jaffray, 2023)
In the current reality of the development of faith and the church, there are challenges in the form of unhealthy teachings that can hinder the growth of true religion. That is why this research aims to analyze and reveal the concept of God's servants based on Titus 1:5-2:10. Then, show and describe the steps to become a servant of God who contributes to the development of the church and society through sound teachings based on Titus 1:5-2:10. The results of this research are that four factors challenge the church in dealing with heresy. However, this challenge is paradoxical because, on the other hand, within this challenge, there are opportunities for the church, especially for community development. The four factors include, First, Religious Pluralism and Moral Relativism. It is essential to properly understand the moral values taught by the religious scriptures so that they can be the primary key to opening the way for evangelization missions. Second, the influence of media and technology. The presence of social media will become an increasingly important service object for maintaining connections among its people—third, Heretical Teachings. The church needs to act firmly to fight the practices of heretics who try to distort the truth to suit their wishes. Fourth, Materialism and Worldly Pleasures. No human wealth can buy life or health. Therefore, this "empty space" can provide an opportunity for God's servants, who are equipped with sound doctrine, to bring people to the needs of eternity rather than mortal.